Preclinical models of diabetic wound healing: A critical review - Sanapalli, Bharat Kumar Reddy; Yele, Vidyasrilekha; Singh, Mantosh Kumar; Thaggikuppe Krishnamurthy, Praveen; Karri, Veera Venkata Satyanarayana Reddy (Biomedicine & pharmacotherapy, 2021)
The treatment of diabetic wounds (DWs) is always challenging for the medical community because of its multifaceted pathophysiology. Due to practical and ethical considerations, direct studies of therapeutic interventions on human subjects are limited. Thus, it is ideal for performing studies on animals having less genetic and biological variability. An ideal DW model should progress toward reproducibility, quantifiable interpretation, therapeutic significance, and effective translation into clinical use. In the last couple of decades, various animal models were developed to examine the complex cellular and biochemical process of skin restoration in DW healing. Also, these models were used to assess the potency of developed active pharmaceutical ingredients and formulations. However, many animal models lack studying mechanisms that can appropriately restate human DW, stay a huge translational challenge. This review discusses the available animal models with their significance in DW experiments and their limitations, focusing on levels of proof of effectiveness in selecting appropriate models to restate the human DW to improve clinical outcomes. Although numerous newer entities and combinatory formulations are very well appreciated preclinically for DW management, they fail in clinical trials, which may be due to improper selection of the appropriate model. The major future challenge could be developing a model that resembles the human DW environment, can potentiate translational research in DW care. [Display omitted] •Diabetic wound (DW) research is limited by a lack of consistent animal models capable of mimicking its pathophysiology.•Although several models are available for DW research, choosing one remains a logical approach for translational research.•Analyzing these research gaps will provide investigators with future insights in developing a reproducible DW model.•Possibly, the best models was structured with an end goal that these disabilities are practically identical.•Advancement in genetic manipulation of animal models may result in a quality research product transition to clinical use.